2023
DOI: 10.3390/pr11020408
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Treatment and High-Intensity Ultrasound Processing to Evaluate the Chemical Profile and Antioxidant Activity of Amazon Fig Juices

Abstract: The present paper evaluated the influence of heat treatment (HT) and high-intensity ultrasound (HIUS) on the chemical profile of the Amazon fig (Ficus subapiculata, Moraceae) juices. Antioxidant activity, quantification of carotenoids, total phenolic compounds (TPC), pH, titratable acidity, soluble solids, color and chemical profile (NMR) were evaluated. Treatments did not change the pH (3.4–3.5), titratable acidity (0.044–0.048%) and soluble solids (2.3–2.4 °Brix). The highest antioxidant activity (DPPH, ABTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a recent study, extracts of phenolic compounds with ultrasound revealed that this treatment can enhance the extraction of polyphenols from fruits [35]. The extraction of thermostable bioactive compounds such as gallic acid derivatives can be enhanced up to a certain temperature level.…”
Section: Quantification Of Bioactive Compounds By Hplc-dadmentioning
confidence: 99%
“…In a recent study, extracts of phenolic compounds with ultrasound revealed that this treatment can enhance the extraction of polyphenols from fruits [35]. The extraction of thermostable bioactive compounds such as gallic acid derivatives can be enhanced up to a certain temperature level.…”
Section: Quantification Of Bioactive Compounds By Hplc-dadmentioning
confidence: 99%
“…Ultrasonication is a novel method for processing food that does not use heat and instead relies on ultrasound to retain the natural flavor and nutritional value of fruit juices. Unlike traditional heat treatment, which can have adverse effects, ultrasonication can be gentle and efficient. Extensive research by the scientific community on the impact of ultrasound has highlighted the benefits of this innovative food processing technique. Using ultrasonication, food manufacturers can create high-quality products that meet the needs and demands of consumers who want fresh, healthy, and delicious foods.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, several scientific studies have examined the potential benefits and drawbacks of employing ultrasound technology to process cashew apple juice. One of the notable advantages of using ultrasound in the juice treatment process is that it can significantly enhance the contents of bioactive compounds present in the juice, particularly vitamin C. , This could be attributed to the fact that ultrasound can disrupt the cell walls of the fruit and release more nutrients into the juice, ,, In addition, research has demonstrated that sonication can effectively reduce the enzymatic browning of the juice, which is a common problem in fruit processing. This enzymatic browning is caused by the presence of polyphenol oxidase and can cause a reduction in the nutritional value and visual appeal of the juice. ,,, Using ultrasound can inhibit the enzyme activity, thereby preventing the juice from darkening and maintaining its natural color during storage.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound processing is among the many non-thermal processes available for the food industry. The ultrasonic treatment is effective against microorganism spoilage and undesired enzymatic effects [10][11][12][13][14] and has the benefit of preserving or improving the nutritional quality of several fruit juices [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of sonication on vitamin C, carotenoids, phenolics, and other antioxidants have been addressed for many juices, such as beetroot [15], fig [16], strawberry [17], kutkura [18], melon [19], pineapple [20], grape [21], and several other fruit juices. Reports on the ultrasonic treatment of fruit juices show divergent results regarding the effects of this technology.…”
Section: Introductionmentioning
confidence: 99%